Preprocedural Cross-Sectional Imaging Prior to Percutaneous Peripheral Arterial Disease Interventions. (February 2020) - Itoga, Nathan K.; Ho, Vy T.; Tran, Kenneth; Chandra, Venita; Dalman, Ronald L.; Harris, Edmund J.; Lee, Jason T.; Mell, Matthew W.
Preprocedural cross-sectional imaging (PCSI) for peripheral artery disease (PAD) may vary due to patient complexity, anatomical disease burden, and physician preference. The objective of this study was to determine the utility of PCSI prior to percutaneous vascular interventions (PVIs) for PAD. Patients receiving first time lower extremity angiograms from 2013 to 2015 at a single institution were evaluated for PCSI performed within 180 days, defined as computed tomography angiography (CTA) or magnetic resonance angiography (MRA) evaluating abdominal to pedal vasculature. The primary outcome was technical success defined as improving the target outflow vessels to <30% stenosis. Of the 346 patients who underwent lower extremity angiograms, 158 (45.7%) patients had PCSI, including 150 patients had CTA and 8 patients had MRA. Of these, 48% were ordered by the referring provider (84% at an outside institution). Preprocedural cross-sectional imaging was performed at a median of 26 days (interquartile range: 9-53) prior to the procedure. The analysis of the institution's 5 vascular surgeons identified PCSI rates ranging from 31% to 70%. On multivariate analysis, chronic kidney disease (odds ratio [OR] = 0.35; 95% confidence interval [CI]: 0.17-0.73) was associated with less PSCI usage, and inpatient/emergency department evaluation (OR = 3.20; 95% CI: 1.58-6.50) and aortoiliac disease (OR = 2.78; 95% CI: 1.46-5.29) were associated with higher usage. After excluding 31 diagnostic procedures, technical success was not statistically significant with PSCI (91.3%) compared to without PCSI (85.6%), P = .11. When analyzing 89 femoral–popliteal occlusions, technical success was higher with PCSI (88%) compared to procedures without (69%) P = .026. Our analysis demonstrates that routine ordering of PCSI may not be warranted when considering technical success of PVI; however, PCSI may be helpful in treatment planning. Further studies are needed to confirm these findings in another practice setting, with more prescriptive use of PCSI to improve procedural success, and thereby improve the value of PCSI.